Increasing Student's Speaking Ability Through Guessing Game Techniques For the Eighth Graders of MTs NW 02 Rensing: East Lombok in The School Year 2021/2022 - Safari, M. Ubaidillah Karomi (International Conference on Islamic Studies, 2021)
This study focused on three cases such as (a) Increasing students’ speaking ability in expressing their needs willingness or to communicate directly with their friends in school. (b) To enable students communicate in English correctly. (c) to know how the process of the technique and the result of students’ speaking ability after taught by using guessing game technique.The study problems were: 1) How does the process of guessing game technique increasing students; speaking ability? 2) To what extent the guessing game technique increase the students’ speaking ability? 3) How does teacher implements the guessing game technique in teaching speaking in order to increase students’ speaking ability?. This study was classroom action research. The subjects of the study were students at Eight grades of MTs NW 02 Rensing. the numbers of students are 42. The technique of collecting data used observation, non observation and documentation. The technique of data analysis used individually and classically.The result of study regarded to the minimum completeness criteria (KKM) which dicided by government on 2013 curriculum. The KKM is devided into three level such as A) Complexity: High=1, Medium=2, Low=3. B) Carrying capacity: High=3, Medium=2, Low=1. C) Intake: High=3, Medium=2, Low=1. The result at the first cycle showed there were only 28 students who met the criteria of completeness with HIGH category. In the second cycle there was an improvement of students who passed namely 37 students with percentage of 80.76 with 3.38 % of impovement. Thus, it could be concluded by implementing the guessing game technique in teaching English could increase students’ speaking ability.